Association of TFPI polymorphisms rs8176592, rs10931292, and rs10153820 with venous thrombosis: A meta-analysis. Issue 12 (March 2019) - Zhang, Yunhong; Pang, Aimei; Zhao, Lin; Guo, Qiang; Zhang, Zhen; Zhu, Xiaoxiao; Wei, Ran; Yin, Xunqiang; Wang, Bin; Li, Xia
Abstract: Background: Tissue factor pathway inhibitor ( TFPI ) polymorphisms are known to be involved in venous thrombosis; however, any correlation between the TFPI polymorphisms rs8176592, rs10931292, and rs10153820 and venous thrombosis remains controversial. This meta-analysis aimed to elucidate the relationship between these TFPI polymorphisms and the susceptibility to venous thrombosis. Methods: A literature search for relevant studies was conducted in PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang Med Online databases. Odds ratios (ORs) and their corresponding 95% confidence intervals (95% CIs) were calculated using fixed-effect/random-effect models by the STATA 12.0 software. Sources of heterogeneity were analyzed by subgroup analysis. Results: Eleven case-control studies involving 3740 subjects (1362 venous thrombosis patients and 2378 healthy controls) were included. The TFPI rs8176592 polymorphism was associated with increased risk of venous thrombosis in the whole population, while no significant association was found between rs10931292/rs10153820 and venous thrombosis. In subgroup analysis based on ethnicity, an increased risk was observed with rs8176592 polymorphism in Asians (Recessive model, OR = 1.48, 95% CI = 1.06–2.07, P  = .023). An increased risk associated with rs10931292 was identified in non-Asians (Recessive model, OR = 1.42, 95% CI = 1.03–1.97, P  = .033). No significant association was found in either Asians or non-Asians with the rs10153820 polymorphism. In subgroup analysis based on source of controls, increased risks were identified in the hospital-based group with rs8176592 polymorphism and in the population-based group with rs10931292 polymorphism, whereas decreased risk was identified in the hospital-based group with the rs10931292 and rs10153820 polymorphisms. Conclusion: Meta-analysis suggested that different TFPI polymorphisms may have different associations with venous thrombosis. TFPI rs8176592 polymorphism may increase the risk of venous thrombosis, especially in Asians and hospital-based patients. The TFPI rs10931292 polymorphism may increase the venous thrombosis risk for both non-Asians and population-based patients. Moreover, rs10931292 and rs10153820 polymorphisms of TFPI may decrease the risk of venous thrombosis for hospital-based patients.